2012
DOI: 10.1002/jip.1356
|View full text |Cite
|
Sign up to set email alerts
|

Prosecution Rate and Quality of the Investigative Interview in Child Sexual Abuse Cases

Abstract: One suggested reason for the low prosecution rate in child sexual abuse cases is the poor quality of the interviews. The present study examined the extent to which a number of aspects of interview quality were used by interviewers at a Children's Advocacy Centre in Sweden. Furthermore, the relationship between aspects of interview quality and the prosecution rate was examined. Transcripts of investigative interviews with 3‐year‐old to 16‐year‐old children who all reported on sexual abuse were assessed (n = 32)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…However, interview quality was not directly related to confidence of guilt decisions, which was counter to predictions and the extant literature (e.g., Buck, Warren, & Brigham, 2004;Buck, London, & Wright, 2011;Castelli et al, 2005; but see Hagborg, Strömwall, & Tidefors, 2012). Instead, interview quality had a significant, indirect effect on confidence of guilt via child credibility.…”
Section: Interview Qualitycontrasting
confidence: 83%
“…However, interview quality was not directly related to confidence of guilt decisions, which was counter to predictions and the extant literature (e.g., Buck, Warren, & Brigham, 2004;Buck, London, & Wright, 2011;Castelli et al, 2005; but see Hagborg, Strömwall, & Tidefors, 2012). Instead, interview quality had a significant, indirect effect on confidence of guilt via child credibility.…”
Section: Interview Qualitycontrasting
confidence: 83%
“…Pipe et al (2013) found that criminal charges were more likely to be filed in child abuse cases in one investigative center after interviewers were trained in the NICHD protocol, a method of increasing the quality of interviews, than before the protocol. Hagborg et al (2012) found no significant relationship between interview quality and prosecution in a Swedish Barnahus, but the sample was only 32 child interviews.…”
Section: Evidencementioning
confidence: 75%
“…In Smith and Goretsky-Elstein (1993) survey, 62% of responding prosecutors reported that they sometimes or very often rejected cases because the victim was too young, and 48% because of teenager noncredibility. Two studies found that adolescents were more likely than younger school age children to have their cases prosecuted (references available upon request), while Cross et al (1994) found no difference between these groups and Hagborg et al (2012) found no age effect. Several studies have found that prosecution of child sexual abuse was more likely when victims were girls (e.g., references available upon request), though Brewer et al (1997) found no difference.…”
Section: Child Age and Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviewing child witnesses is arguably a special case within investigative interviewing ( Hagborg, Stromwall, & Tidefors, 2012 ; see also Chapter 1, this volume). The National Institute of Child and Human Development (NICHD) protocol was developed to ensure that child witnesses are interviewed in a way that makes their testimony useful and reliable ( Lamb, Hershkowitz, Orbach, & Esplin, 2008 ).…”
Section: Investigative Practicesmentioning
confidence: 99%